2023
DOI: 10.2174/1573396318666220819151154
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Bilirubin in Preventing Retinopathy of Prematurity

Abstract: Background: One of the most common problems in preterm neonates is retinopathy of prematurity (ROP). It has been shown antioxidants may be effective in preventing development and progression of ROP. Considering the antioxidant properties of bilirubin, we decided to investigate the bilirubin level in neonates with ROP and compare it with healthy neonates. Methods: This case-control study was performed on VLBW neonates admitted to the NICU of Ghaem Hospital in Mashhad between 2014-2020 years for Jaundice evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The impact of bilirubin levels on the development of ROP has been the subject of debate in earlier publications. Higher levels of bilirubin in neonates may serve as a preventative measure against ROP, according to a recent case-control study [ 31 ]. Additionally, ROP is thought to be less severe when bilirubin levels are higher [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of bilirubin levels on the development of ROP has been the subject of debate in earlier publications. Higher levels of bilirubin in neonates may serve as a preventative measure against ROP, according to a recent case-control study [ 31 ]. Additionally, ROP is thought to be less severe when bilirubin levels are higher [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of bilirubin in neonates may serve as a preventative measure against ROP, according to a recent case-control study [ 31 ]. Additionally, ROP is thought to be less severe when bilirubin levels are higher [ 31 ]. Dejonge revealed no significant difference in the average duration of phototherapy on ROP development but found an association between ROP development and bilirubin levels instead [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, phototherapy may weaken the protective antioxidant effect of bilirubin on cell membranes, making them more susceptible to injury that could result in cell apoptosis. Boskabadi et al found that higher bilirubin levels in preterm newborns may act as a protective factor against ROP [33]. Phototherapy itself causes oxidative stress.…”
Section: Prophylactic or Preventive Phototherapymentioning
confidence: 99%
“…Recently, a Mendelian randomization case-control study reports that genetic variants within the CYP2R1 locus would reduce liver 25-hydroxylase activities and the resultant low blood levels of 25(OH)D are linked with increased non-infectious uveitis/scleritis risk at an OR = 6.42 [ 40 ]. Interestingly, excessive blood unbound bilirubin is suggested to be a protective factor in specific conditions, including in neonates to reduce the severity of retinopathy of prematurity (ROP) [ 41 ], and in patients with diabetic mellitus or impaired glucose tolerance to protect against DR [ 42 ].…”
Section: Epidemiological Evidence and Public Health Significancementioning
confidence: 99%